Systematic review of the effects of acute stress in binge eating disorder. (6th September 2018) - Naish, Katherine R.; Laliberte, Michele; MacKillop, James; Balodis, Iris M.
Abstract: Binge eating disorder (BED) is characterized by recurrent episodes of eating an excessive amount of food over a discrete time period, while feeling a loss of control over one's eating. Although stress is one of the most commonly reported triggers of binge eating in individuals with BED, there has been little work examining the stress response specifically in individuals with the disorder. In this review, we examine what is known about how individuals with BED respond to acute stressors. A systematic literature search identified 14 relevant articles that report on the effects of experimentally induced stress on objective measures. Dependent measures that have been examined include changes in the levels of hormones such as cortisol and ghrelin, cardiovascular function, ad libitum food intake and eating rate. In this review, we describe the published findings and discuss their implications in the context of the wider literature. Overall, we found partial evidence that BED is associated with a heightened response to stress. Given the inconsistencies between studies, we suggest that reported differences between individuals with and without BED might be driven by factors that are correlated with, but not specific to, BED. We suggest that two priorities for this research area are to identify factors that modulate the stress response in individuals with BED, and to address the underrepresentation of males in this literature.